Pengaruh Model Problem Based Learning Terhadap Implementasi Pembelajaran PAI Siswa Madrasah Diniyah Nurul Huda Pasuruan - Riawati Azizah (TARBAWI : Jurnal Pendidikan Agama Islam, 2022)
ABSTRACTThe purpose of this study was to reveal the implementation of Islamic Religious Education learning in the daily lives of students at Madrasah Diniyah Nurul Huda Pasuruan. The subjects in the study were students of grade 3 at Madrasah Diniyah Nurul Huda Pasuruan. The approach used in this research is qualitative research with a case study approach. Data collection techniques in this study were observation, interviews, and documentation. Data analysis techniques are data collection, data reduction, and drawing conclusions. The results showed that the implementation of the Problem Based Learning (PBL) learning model by the teachers at Madrasah Diniyah Nurul Huda Pasuruan could provide students with understanding to implement what they had learned into their daily lives. Even though in cycle I there was not entirely an increase in student implementation, but in cycle II there had been an increase. So the conclusion from the discussion of this research is that the application of the Problem Based Learning (PBL) model has a positive impact on students' ability to implement Islamic Education learning that has been obtained by students into their real life.Keywords: Implementation, PAI, Problem Based Learning Model